Web-based psychosocial interventions for survivors of child sex tourism and their families: a rethink of counselling - Bah, Yahya Muhammed; Artaria, Myrtati Dyah; Suen, Mein-Woei (International Journal of Research in Counseling and Education, 2021)
Daily, in almost every part of the world, series of maltreatment are meted on the children. Because of their vulnerability, the time has come to take serious actions and unreserved measures to end this inhumane treatment and support the victims and their communities. Children are innocent beings and are the last hope of every community and nation and deserve a decent and safe environment to grow to the fullest. This is a fundamental human right as capsulated in the United Nations Convention on the Rights of the Child (UNCRC), an international legal instrument of universal significance. A systematic review of the works of literature using information collected from different sources was actuated. Google search engine, google scholar, web of science, and Scopus database were used to search for these articles. During the search, combinations of words and phrases were used to ensure articles reflected the most current knowledge and scholarly works. The systematic searches beget varied and voluminous articles that had to be sieved not only to meet the inclusion and exclusion criteria but also to ensure the fundamental objectives of the study are wrangled. In summary, the potentials of web-counseling include but are not restricted to unlimited access and improved seeking behavior, affordability, convenience, limited pressure, permanent record availability, anonymity, independence and autonomy, empowerment, geographical barriers elimination, less feeling shy, freedom of expression, confidentiality, and privacy, efficiency and effectiveness improvement, all-time access to multiple therapists, resources with no transport cost and hassle, and client-driven therapy sessions